BOOK REVIEW : The Appearances of Memory. Mnemonic Practices of Architecture and Urban Form in Indonesia - Cuthbert, Alexander R. (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2014)
-
Keywords: -